Moderating effect of teacher–student relationship and mediating role of self-efficacy on the relationship between peer-assisted learning and mathematics performance - Asare, Bright (Frontiers in Education, 2025)
PurposeThe teacher–student relationship and self-efficacy will amplify the positive effect of peer-assisted learning on mathematics performance. A strong teacher–student relationship provides a supportive foundation, while higher self-efficacy equips students with the confidence and resilience to fully benefit from peer-assisted learning. This study examined the effect peer peer-assisted learning on mathematics performance as well as the moderating effect of the teacher–student relationship and the mediating effect of self-efficacy on the relationship between students’ mathematics performance and peer-assisted learning among students.Design/methodology/approachFor this study, a descriptive-correlation design was used. Three hundred and fifty-one students made up the study’s sample size. Stratified simple random sampling techniques were used to select respondents for this study. A structured questionnaire was employed to collect data from targeted respondents. Structural Equation Modeling (SEM) run in Amos (v.23) was used to address the proposed hypothesized paths for this study.FindingsThis study’s findings revealed that teacher–student relationship, self-efficacy, and peer-assisted learning had a positive and statistically influenced mathematics performance. Moreover, self-efficacy somewhat mediates the relationship between peer-assisted learning and mathematics performance. Finally, the association between peer-assisted learning and students’ mathematics performance was positively and considerably moderated by the teacher–student relationship.Originality/valuePrevious research has looked at how peer-assisted learning, teacher–student relationships, and self-efficacy influence mathematics performance. To contribute to the literature, this study examines the moderating and mediating effects of teacher–student relationships and self-efficacy on the relationship between peer-assisted learning and mathematics performance.